Polyphenols and Microbiota Modulation: Insights from Swine and Other Animal Models for Human Therapeutic Strategies - Andrei Cristian Anghel; Ionelia Țăranu; Alina Orțan; Simona Marcu Spinu; Mihaela Dragoi Cudalbeanu; Petronela Mihaela Rosu; Narcisa Elena Băbeanu (Molecules)
High consumption of ultra-processed foods, rich in sugar and unhealthy fats, has been linked to the onset of numerous chronic diseases. Consequently, there has been a growing shift towards a fiber-rich diet, abundant in fruits, vegetables, seeds, and nuts, to enhance longevity and quality of life. The primary bioactive components in these plant-based foods are polyphenols, which exert significant effects on modulating the gastrointestinal microbiota through their antioxidant and anti-inflammatory activities. This modulation has preventive effects on neurodegenerative, metabolic, and cardiovascular diseases, and even cancer. The antimicrobial properties of polyphenols against pathogenic bacteria have significantly reduced the need for antibiotics, thereby lowering the risk of antibiotic resistance. This paper advances the field by offering novel insights into the beneficial effects of polyphenols, both directly through the metabolites produced during digestion and indirectly through changes in the host’s gastrointestinal microbiota, uniquely emphasizing swine as a model highly relevant to human health, a topic that, to our knowledge, has not been thoroughly explored in previous reviews. This review also addresses aspects related to both other animal models (mice, rabbits, and rats), and humans, providing guidelines for future research into the benefits of polyphenol consumption. By linking agricultural and biomedical perspectives, it proposes strategies for utilizing these bioactive compounds as therapeutic agents in both veterinary and human health sciences.